EVALUASI PENERAPAN SISTEM KEUANGAN DESA DALAM MENINGKATKAN TRANSPARANSI DAN AKUNTABILITAS: STUDI KASUS DI DESA BENDASARI, KECAMATAN SADANANYA - Yayat Sudaryat; , R.Didi Djadjuli; Ahmad Juliarso; Eet Saeful Hidayat; Lina Marliani (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2025)
The focus of this study is the various challenges faced in managing village finances through the Siskeudes application, especially those related to frequent system errors. This is because operators do not understand how to operate the application because they do not receive sufficient training. The main objective of this study is to assess the effectiveness of the village financial system in Bendasari Village, located in Sadananya District, Ciamis Regency. Using a qualitative descriptive approach, this study collected data through observation, interviews, and documentation. The results of initial observations showed several problems in the use of the SISKEUDES Application. One of them is the inability to understand the data input process due to the short training time (only two days) and unstable internet connections, which cause frequent errors. In addition, additional problems include problems with the database, the need for password updates that hinder application validation, and mismatches between income and expenses entered into the system. This mismatch causes budgeting errors due to debit and credit imbalances. This causes errors in village financial recording.